Mali Financial Sector Assessment Program : The Microfinance Sector - World Bank (Washington, DC, 2016)
While the microfinance sector is extensively used in Mali (about 1 million members often based in rural areas), the sector has experienced a major crisis for over six years. The clean-up of the microfinance remains the most pressing priority for the Malian authorities and the adoption of the emergency plan for the microfinance sector is a key milestone to cleaning up the sector. While the plan addresses the main issues (restructuring or liquidation not viable MFIs; depositors indemnization mechanism; consolidation of active MFIs; reform and strengthening of the national supervisory body), but the implementation remains very challenging in a context of fiscal tightening and donor’s reluctance to intervene. It is only the Government of Mali that can restore confidence in the sector, and only by undertaking the recommendations highlighted in the emergency plan. One of the most sensitive issues will be to manage the liquidation of a few important distressed institutions together with the indemnization of their depositors.